In Silico, In Vitro and In Vivo Pharmacodynamic Characterization of Novel Analgesic Drug Candidate Somatostatin SST4 Receptor Agonists - Boglárka Kántás; Boglárka Kántás; Éva Szőke; Éva Szőke; Éva Szőke; Rita Börzsei; Péter Bánhegyi; Junaid Asghar; Lina Hudhud; Lina Hudhud; Anita Steib; Anita Steib; et al. (Frontiers Media S.A., 2021)
Background: Somatostatin released from the capsaicin-sensitive sensory nerves mediates analgesic and anti-inflammatory effects via its receptor subtype 4 (SST4) without influencing endocrine functions. Therefore, SST4 is considered to be a novel target for drug development in pain, especially chronic neuropathy which is a great unmet medical need.Purpose and Experimental Approach: Here, we examined the in silico binding, SST4-linked G protein activation and β-arrestin activation on stable SST4 expressing cells and the effects of our novel pyrrolo-pyrimidine molecules (20, 100, 500, 1,000, 2,000 µg·kg−1) on partial sciatic nerve ligation-induced traumatic mononeuropathic pain model in mice.Key Results: The novel compounds bind to the high affinity binding site of SST4 the receptor and activate the G protein. However, unlike the reference SST4 agonists NNC 26-9100 and J-2156, they do not induce β-arrestin activation responsible for receptor desensitization and internalization upon chronic use. They exert 65-80% maximal anti-hyperalgesic effects in the neuropathy model 1 h after a single oral administration of 100-500 µg·kg−1 doses.Conclusion and Implications: The novel orally active compounds show potent and effective SST4 receptor agonism in vitro and in vivo. All four novel ligands proved to be full agonists based on G protein activation, but failed to recruit β-arrestin. Based on their potent antinociceptive effect in the neuropathic pain model following a single oral administration, they are promising candidates for drug development.